2011
DOI: 10.1055/s-0031-1277984
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Encephalopathy and Other Brain Disorders Associated with Renal Failure

Abstract: Kidney failure is one of the leading causes of disability and death and one of the most disabling features of kidney failure and dialysis is encephalopathy. This is probably caused by the accumulation of uremic toxins. Other important causes are related to the underlying disorders that cause kidney failure, particularly hypertension. The clinical manifestations of uremic encephalopathy include mild confusional states to deep coma, often with associated movement disorders, such as asterixis. Most nephrologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 21 publications
0
105
2
8
Order By: Relevance
“…The manifestations of this brain disorder include various neurologic symptoms such as movement disorders (tremor, asterixis, myoclonus), cognitive disorders, and alteration in mental status. 10,11 UE presents 3 patterns of imaging findings: basal ganglia involvement, [12][13][14] cortical or subcortical involvement, 15,16 and white matter involvement. 17,18 Basal ganglia involvement is more common in Asian patients with DM.…”
Section: Discussionmentioning
confidence: 99%
“…The manifestations of this brain disorder include various neurologic symptoms such as movement disorders (tremor, asterixis, myoclonus), cognitive disorders, and alteration in mental status. 10,11 UE presents 3 patterns of imaging findings: basal ganglia involvement, [12][13][14] cortical or subcortical involvement, 15,16 and white matter involvement. 17,18 Basal ganglia involvement is more common in Asian patients with DM.…”
Section: Discussionmentioning
confidence: 99%
“…78 Various uremic toxins have been implicated in the pathogenesis of cognitive impairment. 79 DeDeyn et al reported that cerebrospinal fluid and brain levels of some guanidine compounds, such as creatinine, guanidine, guanidinosuccinic acid, and methylguanidine, are substantially elevated in uremic patients. 80 Interestingly, these high toxin concentrations (up to 10-fold higher in CKD patients than in controls) were found in brain regions that play a determinant role in cognition, such as the thalamus, the mammillary bodies, and the cerebral cortex.…”
Section: Potential Causes Of Cognitive Impairment In Patients With Ckdmentioning
confidence: 99%
“…Such cases can present with complex mental changes, confusion, delirium, psychosis, motor disturbances (tremor, myoclonus, asterixis), hyperreflexia, and disturbances of gait and speech-which are more commonly settled on chronic rather than acute failures [5]. Nevertheless, ophthalmoparesis and asymmetric cranial nerve palsies are not common in this setting.…”
Section: Discussionmentioning
confidence: 99%